The p16INK4A/pRb pathway and telomerase activity define a subgroup of Ph+ adult Acute Lymphoblastic Leukemia associated with inferior outcome. Issue 4 (April 2015) - Chien, Wei W.; Catallo, Régine; Chebel, Amel; Baranger, Laurence; Thomas, Xavier; Béné, Marie-Christine; Gerland, Luc M.; Schmidt, Aline; Beldjord, Kheira; Klein, Nathalie; Escoffre-Barbe, Martine; Leguay, Thibaut; et al.
Highlights New prognosis markers are needed in Adult BCP-ALL prospective trials. The p16INK4A/CDK4-6/pRb pathway and telomerase activity were analyzed in 123 cases. These variables appeared as new prognostic markers in the BCR-ABL1+ subgroup. In vitro analysis suggested that this poor prognosis may be related to cell activation. These findings argue for the development of new therapeutic strategies in BCR-ABL1+ ALL.